2019
DOI: 10.1016/j.geoderma.2018.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sorption and bioavailability of herbicides in soil amended with fresh and aged biochar

Abstract: Highlights  Aged biochar removed greater amounts of herbicides from solution than fresh biochar.  Herbicide sorption by aged biochar was attributed to a dissolvable surface coating.  Degradation of picloram in soil was accelerated by the presence of aged biochar.  Slow sorption occurred for terbuthylazine and imazamox in aged biochar amended soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 48 publications
2
24
0
1
Order By: Relevance
“…Coadsorption and pore filling were the mechanisms proposed after the chemical activation. Regarding pesticides, this knowledge is still inconsistent; in a previous work, we found that three highly persistent ionizable pesticides had a completely different sorption behavior over time on the same aged biochar and differences were attributed to the water-soluble fraction [17].…”
Section: Introductionmentioning
confidence: 90%
“…Coadsorption and pore filling were the mechanisms proposed after the chemical activation. Regarding pesticides, this knowledge is still inconsistent; in a previous work, we found that three highly persistent ionizable pesticides had a completely different sorption behavior over time on the same aged biochar and differences were attributed to the water-soluble fraction [17].…”
Section: Introductionmentioning
confidence: 90%
“…Fresh BC from oak wood was prepared by slow pyrolysis at maximum pyrolysis temperature (550 °C) 30 . Two samples of Fresh BC were subjected to aging.…”
Section: Methodsmentioning
confidence: 99%
“…Mesh bags (Mesh Cord Bags, Vaultz®) were used following the procedure indicated in Gámiz et al 31 . Biochar samples were characterized according to Gámiz et al 30,31 . (Table 1) and properties of soil amended with the various BCs (see Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations